1989
DOI: 10.1093/ajcn/50.2.315
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and glycemic responses in healthy humans to native starches processed in different ways: correlation with in vitro alpha-amylase hydrolysis

Abstract: The aim of the study was to elucidate how extracted starches submitted to food processing (or not) can influence plasma insulin and glucose responses in healthy subjects. Native starches from wheat, manihot, smooth peas, or mung beans were tested either raw, as starch gels (boiled and cooled), or cooked and cooled after a preliminary industrial processing: extrusion cooking for wheat, tapioca for manihot, and noodles for mung beans. Eighteen healthy subjects randomly assigned received three different starches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(69 citation statements)
references
References 41 publications
6
61
0
2
Order By: Relevance
“…Sticky rice, with a lower amylose content, was hydrolyzed very rapidly in vitro, producing a hydrolysis graph similar to that with white bread (Granfeldt et al, 1992). Also, the metabolic responses and in vitro rate of starch hydrolysis of gels made from wheat, manihot, and smooth pea starch were inversely related to the amylose content (17-35%) (Bomet et al, 1989).…”
Section: Amylose/amylopectin Ratiomentioning
confidence: 92%
“…Sticky rice, with a lower amylose content, was hydrolyzed very rapidly in vitro, producing a hydrolysis graph similar to that with white bread (Granfeldt et al, 1992). Also, the metabolic responses and in vitro rate of starch hydrolysis of gels made from wheat, manihot, and smooth pea starch were inversely related to the amylose content (17-35%) (Bomet et al, 1989).…”
Section: Amylose/amylopectin Ratiomentioning
confidence: 92%
“…Several authors have shown that food carbohydrates differ in their in vitro digestion rates (Björck & Siljestrom, 1987. Furthermore, some biological biomarkers such as glycemic and insulinemic levels are dependent on the sensibility of food carbohydrates to enzymatic digestion in the intestinal tract (Bornet et al, 1989;Englyst et al, 1999;Araya et al 2002) and a relationship between the in vitro and biological essays has been reported. Some works have demonstrated in adults and obese adolescents an inverse relationship between glycemic index and satiety (Ludwig et al, 1999;Ludwig 2000;Augustin et al, 2002), but in other's investigations the results showed the inverse tendency (Holt et al, 1996;Raben et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that the differences in amylose content may illicit variations in functional characteristics such as digestibility, crystallinity, physical properties, functionality and glycemic indices [7,[13][14]. Such variations can impact on the resulting metabolic effects and susceptibility of the native starch to α-amylase digestion [15,16]. Starch digestibility is of primary significance to health conscious, diabetic and hyperlipidemic individuals as starches that are highly degraded tend to illicit higher insulin demand than those that are less digestible [16].…”
Section: Introductionmentioning
confidence: 99%
“…Such variations can impact on the resulting metabolic effects and susceptibility of the native starch to α-amylase digestion [15,16]. Starch digestibility is of primary significance to health conscious, diabetic and hyperlipidemic individuals as starches that are highly degraded tend to illicit higher insulin demand than those that are less digestible [16]. Jenkins et al [17] reported that easily digested starches have a higher insulin demand than the slower degrading starches.…”
Section: Introductionmentioning
confidence: 99%